Tatalaksana Dermatitis Atopik Pada Anak - Prayogi Miura Susanto (Yayasan Pendidikan Medika Indonesia, 2022)
Atopic dermatitis (AD) or eczema is a skin disease characterized by chronic-recurrence inflammation and most commonly occurs in infancy and childhood. Atopic dermatitis can be treated with various options. The most effective treatment for AD is to control the symptoms or itching sensation that occurs, and restore normal skin barrier conditions. There are five main pillars in the management of AD in children.